SPIRITUALITY IN THE EDUCATIONAL ENVIRONMENT: PROBLEMS OF IMPLEMENTATION AND REALIZATION - Olga Tsybulko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article deals with the problems of implementation and realization of spirituality in the educational space. Particular attention is paid to the importance of recognizing the spiritual component of education, marking the difference between religious and spiritual issues.